(3GdQjGVI GdeGdjI (B/s - (3GdgdHGhi, YHO Gddg Jhajbs ((3GdbGgQI(B: s (3ecJHI GdMQjI(B, s, 2009)
(3WQb MSGH GdaGFOI GdHSjWI , GdNUe GdHSjW h GdbjeI GdMGdjI , GdOaYGJ GdeJSGhjI h GdahGFO GdOhQjI , SOGO GdbQhV h GSJHOGdgG , GdMSGHGJ GdLGQjI , WQb MSGH GdLedI GdeQcHI h GdaGFOI GdeQcHI , NUe h GSJHOGd GdOjhf HaGFOI eQcHI , GdLedI GdeQcHI h GdbjeI GdMGdjI ddOaYGJ GdeJSGhjI , ESJgdGc GdbQhV WhjdI GdCLd HaGFOI eQcHI (B.s
(3LOGhd U(B.387s
Keywords: (3GdQjGVjGJs; (3GdahGFOs; (3GdeGdjIs